LEADERSHIP, CAPACITY OF INNOVATION, AND PERFORMANCES OF THE PESANTREN - Jafar Syahbuddin Ritonga (Journal Analytica Islamica, 2015)
This paper aims to explore performances of the Pesantren: to what extent leadership, as an internal strategic activity, has an effect to improve such performances. The paper will be directed to discuss everything related to theory of Social Entrepreneurship (SE) which aims to explain phenomenon of the Pesantren, as arguably a form of the SEs. In addition, the concept of SE is approached by Contingency Theory as a basis for building the theoretical framework. Finally, the findings of the research reveal that performances of the Pesantren are influenced by leadership, as a Pesantren’s Internal Strategy Activity. It is also concluded that the Pesntren’s Performances will be varied at different levels of Capacity of Innovation